Mechanical Behavior of A MEMS Based Capacitive Energy Harvester - Azizi, Soleyman; Rahimpour, Mohammad; Rad, Loghman Ghaderi (Kurdistan Journal of Applied Research, 2017)
Energy harvesting is defined as a technology that converts the available excess energy in the environment into usable energy for low power consuming electronics. Past researches on vibration energy harvesting has focused mainly on the use of magnets or piezoelectric materials as the basis of energy transduction. This paper presents a new design for extracting energy using an electrostatic capacitive energy harvester which can be considered as a combination of charge constrained and voltage constrain cycles. In previous analyses, the constant charge and constant voltage operation were studied separately, but in this work both of these operations have been studied in a combination with each other. In this paper, the variable capacitor is formed by an out of plane gap closing structure. In order to investigate the mechanical behaviour of the capacitive energy harvester, a rectangular micro plate is considered with geometrical and material properties. Due to the nonlinearity and low displacement amplitude that result from electrostatic force, energy can be generated. In order to study the primer factors for increasing generated energy, geometrical parameters of the system have been changed. Time history of the shuttle mass and micro-plate undergone vibration are illustrated. It must be noted that after several cycle vibration of the plate, it reaches to stability and regular cycles.